MAIZE SEEDING RATE: REPLACING GERMINATION WITH FIELD EMERGENCE AND ACCELERATED AGING - PEREIRA, LUCAS CAIUBI; CORREIA, LARISSA VINIS; MATERA, THAISA CAVALIERI; SANTOS, RAYSSA FERNANDA DOS; BRACCINI, ALESSANDRO LUCCA (International Journal of Maize & Sorghum, 2020)
The objective of this study was to evaluate the suitability of replacing the germination test in the calculation of seed quantity with the results of the field emergence and accelerated aging tests. The experiment was conducted using a randomized block design in a 2x5 factorial scheme: two levels of seed vigor and five levels of seeding safety margin (0, 5, 10, 15 and 20%) using untreated seeds of the hybrid Defender Viptera 3. The evaluated parameters were percentage of germination, field emergence and accelerated aging. The analyzed variable, plant stand, was submitted to analysis of variance at the 5% significance level and, when significant, the results were submitted to the Mean Percentage Error statistical procedure to determine the degree of proximity between forecast and observed values of stand density. The results showed that, requiring a smaller safety margin, the results of field emergence and accelerated aging tests applied in the seeding rate calculation were more accurate than germination for stand density estimation. For so, nevertheless, they required larger amounts of seeds in sowing operation to reach the same stand density obtained with the use of germination test.